State support for agriculture. Directions of the legal mechanism improvement - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2019)
The work is devoted to the legal mechanism of state support for agriculture in the context of interstate integration within the framework of the Eurasian Economic Union. The purpose of the article is to identify possible ways to improve the legal mechanism mentioned on the basis of an analysis of the correlation between the Belarusian legislation, the Eurasian Economic Union law and member states legislation. As a result of the study, new conclusions were formulated concerning the problem of national Belarusian legislation compliance with obligations within the EAEU, harmonization of the member states law regarding state support for agriculture, the content of this legal concept, the need to change the legal regulation of state support for small farming forms.